Leaching losses of Nitrogen, Phosphorus and Potassium from the sandy loam soil of old Brahmaputra floodplain (AEZ-9) under continuous standing water condition - Islam, MN; Rahman, MM; Mian, MJA; Khan, MH; Barua, R (Bangladesh Journal of Agricultural Research, 2015)
An experiment was conducted at the net house of the Department of Soil Science, Bangladesh Agricultural University (BAU), Mymensingh, Bangladesh during February to June (boro season) of 2009. The objective was to find out the leaching loss of N, P, and K in the Old Brahmaputra Floodplain Soil under continuous standing water (CSW) condition. The soil was sandy loam in texture having pH 6.6, total N 0.08%, available P 7.00 mg/kg, exchangeable K 0.07 me/100g soil, and available S 7.5 mg/kg. The experiment was laid out in completely randomized design with three replications. There were six treatments, such as T0 (control), T1 (N120 P25 K60 S20 recommended dose), T2 (N180 P37 K90 S30 kg/ha i.e., 150% of the recommended dose), T3 (75% N of T1 from chemical fertilizer and 25% N from cowdung 2.5 t/ha and PKS of recommended dose from chemical fertilizer on the basis of PKS content in cowdung), T4 (as T1 but N109 kg/ha from USG) and T5 (as T1 but N applied as foliar spray). The nutrients P, K, and S were applied as basal dose in the pots while urea was applied in three equal splits except T4 and T5. One USG per pot was placed after 7 days of transplanting in T4. In T5, urea was applied as foliar spray at 10 days interval. Leachates from individual pots were collected at 15 days intervals to determine the amount of loss of NPK. Results showed that leaching loss of NPK in the sandy loam soil under CSW condition varied widely due to different treatments over time. The total leaching loss of N, P, and K during the growing season varied from 22.23 to 91.21, 0.063 to 1.95, and 35.22 to 42.01 kg/ha, respectively. Application of chemical fertilizer at higher rates resulted in greater loss of nutrients. Integrated approach of fertilizer management could minimize such losses to a great extent. Application of N in the form of USG reduced the N loss significantly. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21987 Bangladesh J. Agril. Res. 39(3): 437-446, September 2014